Effective AC needleless and collectorless electrospinning for yarn production - Pokorny, P; Kostakova, E; Sanetrnik, F; Mikes, P; Chvojka, J; Kalous, T; Bilek, M; Pejchar, K; Valtera, J; Lukas, D (Physical chemistry chemical physics, 2014)
Nanofibrous materials are essential components for a wide range of applications, particularly in the fields of medicine and material engineering. These include protective materials, sensors, cosmetics, hygiene, filtration and energy storage. The most widely used and researched technology in these fields is electrospinning. This method for producing fibers yields highly promising results thanks to its versatility and simplicity. Electrospinning is employed in multiple forms, among which needle and needleless direct current (DC) variants are the most distinctive. The former is based on the generation of just one single jet from a nozzle; hence this fabrication process is not very productive. The latter uses the destabilization of free liquid surfaces by means of an electric field, which enhances the throughput since it produces numerous jets, emitted from the surfaces of rollers, spheres, strings and spirals. However, although some progress in total producibility has been achieved, the efficiency of the DC method still remains relatively low. A further drawback of DC electrospinning is that both variants need a collector, which makes it difficult to combine DC electrospinning easily with other technologies due to the presence of the high field strength within the entire spinning zone. This paper describes our experiments with AC electrospinning. We show that alternating current (AC) electrospinning based on a needleless spinning-electrode provides a highly productive smoke-like aerogel composed of nanofibers. This aerogel rises rapidly from the electrode like a thin plume of smoke, without any need for a collector. Our work shows that AC needleless electrospinning gains its efficiency and collector-less feature thanks to the creation of a perpetually charge-changing virtual counter-electrode composed of the nanofibers emitted. High-speed camera recordings demonstrate the formation mechanism of the nanofibrous plume, which is wafted by an electric wind. This wind's velocity field is experimentally investigated. One potential use of AC needleless electrospinning is demonstrated here by spinning it into a yarn.